(3efXheI aj GdYbGFOs - (3eMeO MSf Hf CHj GdaVds ((3MSf Hf eMeO HGbQ GdMSjfjs)
(3ChdgG (B:s
(3HSe Gddg (B.. (3MeO GdhGLH GdehLhO GdCLd GdbGOQ GdYOd GdMcje GdUeO (B** (3hGdUdhGJ GdHGbjGJ SQeOG Ydi NJGe GdeQSdjf GMeOG (B** (3hBdg GdCFeI GdCeLGOs
(3BNQgG (B:s
...(3cGdHYK hGdUQGW hGdejRGf hGdMSQ hGdLfGf hGdfjQGf hGdYbh hGdbUGU hGdTaGYI deDef ebUQ aj GdWGYI (B..(3JeJs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds